Repeated-sprint training in hypoxia: A review with 10 years of perspective - Faiss, R.; Raberin, A.; Brocherie, F.; Millet, G. P. (Journal of Sports Sciences, 2025)
Over the past decade, numerous studies have investigated an innovative "live low-train high" approach based on the repetition of short (<30 s) "all-out" sprints with incomplete recoveries in hypoxia; the so-called Repeated-Sprint training in Hypoxia (RSH). The aims of the present review are therefore threefold. First, this study summarizes the available evidence on putative additional performance enhancement after RSH comparing to the same training in normoxia (RSN). Second, a critical analysis of underpinning mechanisms discusses how advantages can be obtained through RSH for sea-level performance enhancement. An enhanced microcirculatory vasodilation leading to improved muscle perfusion and/or oxygenation and an increase in muscular phosphocreatine content may help explain the superiority of RSH vs. RSN. Third, the present review aims to provide guidelines for coaches, athletes and scientists to apply RSH interventions with regard to the interval duration, exercise-to-rest ratio and training volume. In conclusion, this review supports repeated-sprint training in hypoxia as an efficient (but not magic) training intervention with 77% of the controlled studies reporting an additional benefit with added hypoxia, mainly for team-, combat- and racket-sports athletes but also for all other sports (e.g. endurance) that require repeated accelerations with lesser fatigue.